Challenges in the Implementation of Interactive Multimedia Using the Discovery Learning Model to Enhance Logical Thinking - Adeliani, Cindy Sri Meidina; Wahyudin, Wahyudin; Megasari, Rani (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
In facing the challenges of the digital era, education in Indonesia must innovate through the integration of technology to produce a superior workforce. Traditional teacher-centered teaching methods have become an obstacle to developing students' logical thinking skills in problem-solving and conclusion-drawing. This research aims to develop and test the effectiveness of website-based interactive multimedia using the discovery learning model on the Entity Relationship Diagram (ERD) topic to enhance students' logical thinking skills. The media development employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), with the interactive multimedia flow designed according to the stages of discovery learning. Effectiveness was measured using a one-group pretest-posttest design with vocational high school students in West Bandung, while the feasibility of the material and media was validated by experts. The improvement in logical thinking skills was measured using the N-gain test. The results showed that the developed interactive multimedia was declared highly feasible by material and media experts. The effectiveness test indicated an improvement in students' logical thinking skills, with an N-gain score in the medium category. However, a detailed breakdown of the improvement per aspect revealed that argumentation skills were moderate, while thought coherence and conclusion-drawing skills remained low. These difficulties were attributed to a lack of student initiative and motivation in discussion and summarizing the material. It is concluded that this interactive multimedia is feasible and effective as an alternative learning medium for training students' logical thinking skills, although further optimization is needed to improve thought coherence and conclusion-drawing abilities.